Russia : Subnational Governments' Fiscal Response to the Economic Downturn - World Bank (Washington, DC, 2017)
The aim of this note is to present and analyze subnational fiscal trends in Russia in the context of overall slowing economic growth and falling oil prices over the last few years. In particular, in 2015, GDP fell by 3.7 percent. Despite efforts to cut expenditures, the federal deficit increased to 2.4 percent of GDP. Subnational governments were also affected by the economic slowdown. Aggregate subnational revenues declined, in real terms, by 6 percent between 2014 and 2015. Revenues from taxes (including shares of federal taxes) fell by 4 percent while federal transfers fell by 13 percent. Nevertheless, the aggregate fiscal performance of subnational governments actually improved over this period. The nadir of subnational government finances occurred in 2013, when the consolidated subnational deficit reached 0.9 percent of GDP. Since then, it has shrunk. In 2015, the deficit was equal to only 0.2 percent of GDP. This was largely achieved by drastic cuts in spending. Spending in the social and infrastructure sectors both fell by 9 percent in real terms between 2014 and 2015. This note examines the fiscal prospects of subnational governments in Russia, focusing particularly on the nature of these spending cuts and whether they are sustainable over the medium term.